# How do you differentiate f(x)=csc(ln(1/x))  using the chain rule?

##### 1 Answer
Nov 22, 2016

$\frac{d}{\mathrm{dx}} \left(f \left(x\right)\right) = \frac{1}{x} \cot \ln \left(\frac{1}{x}\right) \csc \ln \left(\frac{1}{x}\right)$

#### Explanation:

$f \left(x\right)$ composed of two functions $\csc x \text{ "and" } L n x$.
$\text{ }$
So, Differentiating $f \left(x\right)$ is determined by applying chain rule.
$\text{ }$
Let $u \left(x\right) = \ln \left(\frac{1}{x}\right) \text{ " then " } f \left(x\right) = \csc \left(u \left(x\right)\right)$
$\text{ }$
$\frac{d}{\mathrm{dx}} \left(f \left(x\right)\right) = \frac{d}{\mathrm{dx}} \left(\csc x \left(u \left(x\right)\right)\right)$
$\text{ }$
$\textcolor{b l u e}{\frac{d}{\mathrm{dx}} \left(f \left(x\right)\right) = u ' \left(x\right) \times \csc ' \left(u \left(x\right)\right)}$
$\text{ }$
Let us compute $\textcolor{b l u e}{u ' \left(x\right)}$
$\text{ }$
$u ' \left(x\right) = \frac{\textcolor{red}{\left(\frac{1}{x}\right) '}}{\frac{1}{x}}$
$\text{ }$
What is the derivative of 1/x=?
$\text{ }$
The differiation of $\frac{1}{x}$ is determined by applying the quotient rule .
$\text{ }$
$\textcolor{red}{\left(\frac{1}{x}\right) '} = \frac{\left(1\right) ' \times x - \left(x\right) ' \times 1}{x} ^ 2 = \frac{0 - 1}{x} ^ 2 = \textcolor{red}{- \frac{1}{x} ^ 2}$
$\text{ }$
$\textcolor{b l u e}{u ' \left(x\right)} = \frac{- \frac{1}{x} ^ 2}{\frac{1}{x}} = \textcolor{b l u e}{- \frac{1}{x}}$
$\text{ }$
$\text{ }$
Knowing that the derivative of $\csc x \text{ }$is :
$\text{ }$
color(blue)((cscx)'=-cotxcscx
$\text{ }$
Let us compute color(blue)(csc'(u(x))
$\text{ }$
color(blue)(csc'(u(x)))=-cot(u(x))xxcsc(u(x))=color(blue)(-cotln(1/x)xxcscln(1/x)
$\text{ }$
$\textcolor{b l u e}{\frac{d}{\mathrm{dx}} \left(f \left(x\right)\right) = u ' \left(x\right) \times \csc ' \left(u \left(x\right)\right)}$
$\text{ }$
$\frac{d}{\mathrm{dx}} \left(f \left(x\right)\right) = \left(- \frac{1}{x}\right) \times \left(- \cot \ln \left(\frac{1}{x}\right) \times \csc \ln \left(\frac{1}{x}\right)\right)$
$\text{ }$
Therefore,
$\text{ }$
$\frac{d}{\mathrm{dx}} \left(f \left(x\right)\right) = \frac{1}{x} \cot \ln \left(\frac{1}{x}\right) \csc \ln \left(\frac{1}{x}\right)$